Epilepsy and Pregnancy: An Audit of Specialized Care. (6th September 2022) - Li, Jimmy; Toffa, Dènahin Hinnoutondji; Nguyen, Dang Khoa
ABSTRACT: Background: Caring for women with epilepsy (WWE) during pregnancy poses unique challenges. We conducted an audit of the care our epilepsy clinic provided to pregnant WWE. Methods: We performed a retrospective study on all pregnancies followed by an epileptologist at a Canadian tertiary care centre's epilepsy clinic between January 2003 and March 2021. Among 81 pregnancies in 53 patients, 72 pregnancies in 50 patients were analyzed to determine patient-related, follow-up-related, antiseizure-medication-related, and child-related pregnancy characteristics. Univariate analyses were performed to explore if these characteristics were associated with disabling seizure occurrence during pregnancy. Results: Most pregnancies were intended (72%) and occurred in women who used folic acid pre-pregnancy (76%) and who followed recommended blood tests for antiseizure medication (ASM) levels (71%). In 49% of pregnancies, ASM dosage was modified; 53% of these modifications were made in response to ASM blood levels. Most often used ASMs were lamotrigine (43%), followed by carbamazepine (32%) and levetiracetam (13%). One child was born with a thyroglossal duct cyst; our congenital malformation rate was thus 2%. Disabling seizures occurred in 24% of pregnancies. Exploratory analyses suggested that disabling seizure occurrence during pregnancy was associated with younger patient age (p = 0.018), higher number of ASMs used during pregnancy (p = 0.048), lamotrigine usage in polytherapy (p = 0.008), and disabling seizure occurrence pre-pregnancy (p = 0.027). Conclusion: This Canadian audit provides an in-depth description of pregnancies benefiting from specialized epilepsy care. Our results suggest an association between disabling seizure occurrence during pregnancy and lamotrigine usage in polytherapy that warrants further evaluation.